Factors Influencing Hyponatremia in Hospitalized Diabetic Patients- A Cross Sectional Study (Medicine Today, 2014)
Hyponatremia is a very common electrolyte imbalance in admitted diabetic patients which leads to substantial morbidity and mortality. There is no existing record for profiling of hyponatremia in Bangladeshi diabetic subjects. The objective of this study was to find out the factors influencing hyponatremia and associated co-morbidities in admitted diabetic patients of a tertiary care hospital. Samples were selected from all adult nonpregnant diabetic patients with serum sodium level < 135 mmol/L irrespective of their cause of admission. A total number of 115 admitted diabetic patients with hyponatremia were studied. Informations were collected in a semi structured data collection form for analysis. Hyponatremia was found to be more common in the aged (47%) and female populations (63.5%). Vomiting was found to be the most common factor (51.3%) causing hyponatremia in the admitted diabetic patients. Other common factors influencing hyponatremia were diarrhea, sweating, severe hyperglycemia, diabetic ketoacidosis and drugs especially diuretics. The commonest co-morbid condition associated with diabetes was hypertension. Thiazide diuretics should be used with caution in the elderly who are prone to develop hyponatremia. DOI: http://dx.doi.org/10.3329/medtoday.v26i1.21301 Medicine Today 2014 Vol.26(1): 04-08